Human Factors on the Flight Deck Safe Piloting Behaviour in Practice - Ebermann, Hans-Joachim; Scheiderer, Joachim (Springer Berlin Heidelberg : Imprint: Springer, 2013)
What is for a professional pilot required to fly as safe as possible? Written by pilots the book gives a detailed introduction into the basics of accident prevention in air traffic. Explicit background knowledge as well as detailed listings of safety relevant features in human behaviour are included.